Behavior Analysis of Katata Farmer Group Members to Market Development Program with Outcome Mapping Approach - Gherhana Novyany; Mahra Arari Heryanto (Jurnal Penyuluhan, 2019)
GHERHANA NOVYANY. 2017. Behavior Analysis of Katata Farmer Group Members to Market Development Program with Outcome Mapping approach. Under the guidance of MAHRA ARARI HERYANTO, SP., MT.Katata Farmers Group is under the guidance of Universitas Padjadjaran (UNPAD). UNPAD has several programs, one of them is market development program held by Agrologistika Padjadjaran Team. The purpose of this program is to simplify the supply chain of Katata Farmers Group. This program enables farmer groups to innovate their agricultural cultivation. Therefore, there is a change of social behavior and it occurs after the program was implemented. This research using qualitative method with in depth analysis, and outcome mapping used as the analysis tool. Purposive sampling was used in this research. The result of this research explains that there is a change of supply chain of Katata Farmer Group which previously has to supply its products to modern retail supplier. Nowadays, Katata Farmers Group can supply its products directly to modern retailers, Hero Group (Giant). There is a change of behavior in the Katata Farmers Group after implementation of this program, such as the interaction between each actors that involved in market development program are more complex than before the program implementation. Innovation in agricultural cultivation process allows group members to be more developed in performing their farming and recognized in using new technology that can support their bussiness.